Development of Doruma Otoshi Escape Room Media to Train Students’ Coping Skills - Shela Putri Nadhilah Harahap; Dika Sahputra (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to develop the Doruma Otoshi Escape Room as an innovative medium for guidance and counseling to enhance students’ coping skills. Employing a Research and Development (R&D) approach, the study adopts the 4D development model, which encompasses the stages of define, design, develop, and disseminate. The effectiveness of the product is examined through a quantitative method using a One Group Pre-test–Post-test Design. The research subjects include a material expert, a media expert, and students selected through purposive sampling. Data collection is conducted using coping skill questionnaires administered before and after the intervention, along with expert validation sheets. The data are analyzed through feasibility percentages, validity and reliability testing of instruments, gain score calculations, and Paired Sample t-tests. The expected outcome of this research is the establishment of a valid, feasible, and effective Doruma Otoshi Escape Room medium that significantly improves students’ coping skills.